DEVELOPING SPEAKING SECTION OF BUSINESS ENGLISH MATERIALS TO TEACH CULTURE IN INTEGRATED WAY - Yasmin Farani; Karlina Karadila Yustisia (JOALL (Journal of Applied Linguistics and Literature), 2021)
Teaching English Business skills does not merely teach the students to have administration and communication skills needed at the workplace for they will probably encounter and experience working together with people from different cultures and backgrounds as well. To minimize misunderstanding on those intercultural differences, they are expected not only to learn Business English skills but also gain basic knowledge of English culture through the course. This R&D research is a descriptive qualitative research which is intended to develop the Speaking Section of the existing teaching materials of Business English skills. Under the name of ESP I subject, they are taught to the 4th-semester students of Diploma Three in English Program of University of Merdeka Malang as a compulsory subject. In this study, the primary instruments are the researchers themselves and the preliminary questionnaires used serve as the secondary instrument. All the analyzed data are in the form of printed data (questionnaire’s results) and chosen videos taken from YouTube. The expected final results are in the form of written handouts consist of texts and links of selected videos appropriately related to the given topics. It is hoped that they are useful for the students as an alternative method to learn culture in an integrated way.